Hydrothermal analysis of water-Al2O3 nanofluid flow through a sudden expansion channel with an intermediate step: DOI: 10.48129/kjs.15461 - Saha, Sandip; Das, Apurba Narayan (Kuwait Journal of Science, 2022)
This work presents the dynamic behavior of laminar nanofluid hydro-thermal flow phenomena through a sudden expansion channel with the variations in intermediate step length, height and pitch to width ratio. The governing equations have been discretized by means of finite volume method and the system of algebraic equations has been solved by SIMPLE algorithm. The effect of various parameters, viz., Reynolds number (Re ∊ [0-300]), normalized height (B/C = 0.05, 0.1, 0.2, 0.33), normalized length (A/C = 0, 1, 5, 8) and step pitch-width ratio (A/B = 0, 20, 30, 50) on the enhancement of heat transfer (average Nusselt number and friction factor, pressure drop characteristics, friction factor, performance number and thermal resistance factor) have been studied. At various values of A/C and B/C, this work indicates that the average Nusselt number, thermal resistance factor and performance number increase with the increase in Reynolds number, while the value of average Nusselt number decreases when the pitch-width ratio (A/B) increases. In case of hydro-thermal flow phenomena, the configuration associated with B/C provides the better results than the configurations associated with A/B and A/C. An important outcome of this work is that use of the intermediate step can be avoided by considering porous obstacle for enhancing the average Nusselt number, thermal resistance factor and needless to say that this will become very much helpful for various realistic circumstances for triggering additional thermo mechanical loads on the surface.